Promoting gender equality across the sustainable development goals - Walter Leal Filho; Marina Kovaleva; Stella Tsani; Diana-Mihaela Țîrcă; Chris Shiel; Maria Alzira Pimenta Dinis; Melanie Nicolau; Mihaela Sima; Barbara Fritzen; Amanda Lange Salvia; Aprajita Minhas; Valerija Kozlova; et al. (Environment, Development and Sustainability, 2022)
Gender issues, and gender equality in particular, can be regarded as cross-cutting issues in the implementation of the Sustainable Development Goals (SDGs), even though it is unclear how they are taken into account. This study addresses this information gap by performing an assessment of the emphasis on gender issues across all the other 16 SDGs, in addition to SDG5, through a literature review and case study analysis, the basis for the newly developed framework, highlighting specific actions associated to each SDG. The 13 countries addressed in the 16 case studies include China, India, or Australia and illustrate the inclusion of SDG5 into the SDGs. Using an SDG matrix, the SDG targets are analysed. Those where an emphasis on gender equality is important in allowing them to be achieved are listed. The novelty of our approach resides in offering an in-depth analysis of how gender issues interact with the other SDGs, proposing a new analysis framework clearly identifying SDGs 1, 4, 11, 12, 14 and 16 demanding further attention for successful SD gender implementation and illustrating specific areas where further actions may be necessary, which may be used by policy-makers, raising further awareness on gender equality contribution to achieve the SDGs. A set of recommendations aimed at placing gender matters more centrally in the SDGs delivery are presented as a final contribution. These focus on the need for greater awareness and attention to good practices, to achieve successful implementation initiatives.
Keywords: 330; Sustainable development goals (SDGs); Gender equality; SDG5; Gender across SDGs